Hydroxyprogesterone caproate for preterm birth: A situational analysis from the Indian perspective - Pugazhenthan Thangaraju; Shoban Babu Varthya; Prakash Srinivasan Timiri Shanmugam; T.Y. Sree Sudha; Chaitanya Mittal (BMJ Publishing Group, 2021)
Background: Preterm birth can cause morbidity and mortality in addition to trauma or loss to the mother, and present a major financial burden to the family. This risk may be minimized by timely intervention. Objective: To understand the safety and efficacy of hydroxyprogesterone in decreasing the incidence of preterm birth, neonatal complications, and maternal mortality, based on evidence obtained from the Indian scientific literature. Methods: Relevant articles were searched for and retrieved from the databases PubMed, medrXiv, Embase, Cochrane, biorXiv, and arXiv. Results: A total of 62 relevant articles were assessed, and of these, 59 articles did not meet the eligibility criteria. In total, 3 articles which satisfied the criteria and 2 articles sourced from cross references were included in the study. Across these 5 articles, a total of 536 patients received hydroxyprogesterone caproate or placebo for preterm birth. Conclusion: In all five articles, recurrence rate of preterm birth was reduced in the treated group compared to control group. The safety profile of progesterone tends to be better than that of the placebo. The findings of our analysis of individual patient data (IPD) summarizes various clinical trial data, which can assure clinicians that vaginal progesterone administration is effective and well tolerated.